High-performance deformable photoswitches with p-doped graphene as the top window electrode. Issue 1 (18th November 2014) - Li, Rongjin; Liu, Zhaoyang; Parvez, Khaled; Feng, Xinliang; Müllen, Klaus
Abstract : Deformable polymer photoswitches with p-doped single layer graphene as the top window electrode exhibit an on/off ratio as high as 8.5 × 10 5 . Abstract : Deformable polymer photoswitches with p-doped single layer graphene as the top window electrode exhibit excellent photoresponse with an on/off ratio as high as 8.5 × 10 5 . The charge-transfer doping of graphene results in better charge separation and collection efficiency and the structure of the top electrode minimizes the dark current.